2006
DOI: 10.1111/j.1469-7580.2006.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of myocardial bridges to coronary artery dominance in the adult human heart

Abstract: Myocardial bridging is recognized as an anatomical variation of the human coronary circulation in which an epicardial artery lies in the myocardium for part of its course. Thus, the vessel is 'bridged' by myocardium. The anterior interventricular branch of the left coronary artery has been reported as the most common site of myocardial bridges but other locations have been reported. The purpose of this study was to provide more definitive information on the vessels with myocardial bridges, the length and depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
87
8
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 41 publications
17
87
8
11
Order By: Relevance
“…Myocardial bridging has been described as early as 1737 (Rayman, 1737) and have been described since with a wide range of frequencies reported. In one study of 200 adult human hearts collected from autopsies, myocardial bridges were found in 34.5% with a mean length of 31 mm and a mean depth of 12mm (Loukas et al, 2006). The most common site of myocardial bridging was over portions of the left anterior descending coronary artery (LAD).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Myocardial bridging has been described as early as 1737 (Rayman, 1737) and have been described since with a wide range of frequencies reported. In one study of 200 adult human hearts collected from autopsies, myocardial bridges were found in 34.5% with a mean length of 31 mm and a mean depth of 12mm (Loukas et al, 2006). The most common site of myocardial bridging was over portions of the left anterior descending coronary artery (LAD).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…These differences are possibly due to the number of samples evaluated and to the divergence of criteria used by the authors to perform these characterizations. Diverse studies conducted in human hearts similarly report a wide range of occurrence of the right coronary dominance pattern: Lower incidences within a range of the 48-70% (Schlesinger, 1940;Cavalcanti et al, 1995;Ortale et al, 2004;Kaimkhani et al, 2005;Loukas et al, 2006), medium incidences within a range of 70-84% (Blunk and DiDio, 1971;DiDio and Wakefield, 1975;Hadziselimovic, 1981;Sahni and Jit, 1990;Kalpana, 2003;Pessa et al, 2004;Ballesteros et al, 2007) and high incidences between 85 and 90% (James, 1965;Penthe et al, 1976;Nerantzis et al, 1996). No studies have been conducted in swine to typify right dominance in depth; our series found that mild right dominance (subtype I) was most common, unlike common findings in humans, where a higher incidence of moderate right dominance is described.…”
Section: Discussionmentioning
confidence: 99%
“…Literature reports in humans present frequencies of between 7-26% (Polacek and Zechmeister, 1958;Zbigniew and Mikusek, 2000;Ortale et al, 2004;Loukas et al, 2006;Ballesteros et al, 2007). A balanced circulation expresses an equitable distribution of the irrigation of the diaphragmatic aspect of the heart by the coronary arteries and their branches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dominant artery refers to the coronary artery providing the posterior interventricular branch (PIB) which supplies the posterior ventricular septum and frequently part of the posterolateral wall of the left ventricle (Pelter et al, 2011). The RCA is usually dominant with varying incidence ranging from 55 % to 89.6 % (Angelini et al, 2002;Kim et al, 2006;Loukas et al, 2006;Altin et al, 2015;Standring et al). and right ventricle (Drake et al, 2014).…”
Section: Introductionmentioning
confidence: 99%